2020
DOI: 10.31557/apjcp.2020.21.9.2733
|View full text |Cite
|
Sign up to set email alerts
|

Association between Low Fruit and Vegetable Consumption and Colorectal Polyps in Thailand

Abstract: Objective: This study aimed to evaluate the association between low fruit and vegetable consumption and colorectal polyps. Methods: A retrospective study was conducted among 1,228 participants aged 50-65 years who completed 2-time colonoscopy exams at the first and the fifth year of a colorectal screening program. Consuming less than one serving of fruit and vegetable daily was rated as low. Colorectal polyps from colonoscopy findings were recognized in 3 types: hyperplastic, low risk and high risk adenomatous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Red meat is classified by the IARC as “probably carcinogenic” to humans. In addition, vegetable consumption was significantly higher in controls than in cases with multiple polyps, which also agrees with previous studies ( 46 , 47 ). For example, two studies, one cohort and one case-control, found that the risk of colorectal polyps is increased with lower consumption of cooked green vegetables ( 39 ) and fruits and vegetables ( 40 ), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Red meat is classified by the IARC as “probably carcinogenic” to humans. In addition, vegetable consumption was significantly higher in controls than in cases with multiple polyps, which also agrees with previous studies ( 46 , 47 ). For example, two studies, one cohort and one case-control, found that the risk of colorectal polyps is increased with lower consumption of cooked green vegetables ( 39 ) and fruits and vegetables ( 40 ), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Our research evidenced the higher consumption of fruits as a protective factor in the development of CRC, which is consistent with a series that recently demonstrated the importance of fruit and vegetable intake as protective factors for this type of cancer [21]. Similarly, a diet poor in fruits and the presence of high-risk adenoma polyps were significantly associated with increasing the probability to develop CRC [22]. Since both vegetables and fruits are considered good sources of fiber, folic acid, B vitamins, minerals, and antioxidants, their protective properties could lie in the decreased gastrointestinal transit time, which leads to reduced concentrations of carcinogenic compounds [23].…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study also revealed that the increase in the consumption of vegetables and fruits significantly reduced the likelihood of developing colorectal polyps. The association between dietary fiber and colon cancer has been under investigation for three decades; however, no definite association has been recognized [ 36 , 37 ]. Aune et al reported that a higher proportion of fiber in everyday dietary regimens can reduce the recurrence rate of colorectal adenomas [ 38 ].…”
Section: Discussionmentioning
confidence: 99%